К вопросу о нормировании модифицированной эпоксидной смолы марки УП-666-4 в воздухе рабочей зоны - Теплова, Т.Е.; Богатырева, Е.В.; Ли, Я.Б.; Василенко, И.В.; Мухин, В.В. (Актуальні проблеми транспортної медицини, 2005)
Epoxy resin (ER) is widely used in motor- and aircraft industry and shipbuilding. The task of the work presented is to give toxicological and hygienic estimation of a modified ER UP- 666. Its main toxicological volatile components are epychlorhydrin (EChG) and toluene. ER UP-666-4 is a non toxic substances - LD50 per oral is above 5000 mg/kg by parameters of acute toxicity. The threshold of a single inhalation influence (LIMac) is at the level 58,0±2,3 mg/m3 (by EEG). Under chronic inhalation influence of volatile components ER UP-666-4, concentration at the level 1,35±0,05 mg/m3 (by EChG ) is the threshold of chronic influence (LIMchr) by allergenic effect. High concentrations of volatile components UP-666-4 have general toxic, mutagenic, allergenic effect which caused the development of glomerulonephritis. The workers engaged in ER production (UP-666- 4) with average shift concentrations of volatile components in the working environment at the level of 1-1,5 mg/m3 (EChG) a direct contact of the resin with the workers' skin was not excluded; as a result there was sensibilization of the body to EChG and renal allergens, development of contacted and allergic dermatites, an increase of the upper respiratory tract diseases, deviation of biochemical indices of blood and urine. On the basis of the trial conducted PAC of the volatile components of epoxy resin UH-666-4 in the working environment at the level 0,1 mg/m3 (by EChG) has been substantiated and the first class of danger with the mark "A" (allergen). Hygienic limits of the safe use of the modified ER UH-666-4 and preventive measures of its toxic influence have been worked out.